Effect of heeled shoes on joint symptoms and knee osteoarthritis in older adults: a 5-year follow-up study - Perry, TA; Dando, C; Spector, TD; Hart, DJ; Bowen, C; Arden, N (Wiley, 2021)
Objective Our aims were to examine the effects of heeled shoes on incident knee osteoarthritis (OA) and joint pain.